Enhancing privacy through spatial design for teenage girls in orphanages in Mashhad, Iran - Milani, Nazanin Salehi (2014)
The institutional child care design for teenage girls of Mashhad, Iran was studied. Since 1980, the beginning of the Iran-Iraq war, the number of orphaned children has increased dramatically and currently there are around 21000 individual orphans in Iran. One of the most important aspects in caring for unaccompanied teenage girls successfully is the environment of the institutions they are housed in. Architectural design of institutional care has a prominent role regarding successful caring of unaccompanied teenage girls. Unfortunately, the majority of the buildings in Mashhad have not been designed basically for the purpose of orphanages, which contributes to unsuccessful institutional care of children. Lack of privacy is one of the most important factors for teenage girls as a result of overcrowding in child care institutions in Mashhad. In addition, the main organization, Behzisti of Iran, does not follow their own rules in building institutions and only economical issues are considered as a criterion for building institutions. A few previous studies are examined in terms of its contribution to understand teenage girls’ needs and to improve orphanage design. However, there are no specific rules for living space for orphaned teenage girls’ aged (between the ages of 12 and 18) where their privacy preferences are considered. This study identified the most important orphaned teenage girls’ privacy preferences for their own space and also the suitable measurement and size of the places for them in terms of privacy. Mixed quantitative and qualitative approach was employed to study the teenage girl’s privacy in order to find appropriate size of places at institution for teenage girls with respect to teenage girl’s privacy preference. Five institutions were selected. Sixty-eight orphaned teenage girls were accommodated in the 5 selected institutions and requested to answer to questionnaire. The findings of this study verified that the participants’ backgrounds especially their age which became a critical issue and gave an impact on their visual preferences. The results of the present study showed that a large number of respondents unsatisfied regarding to spatial privacy towards interior spaces and location of their institution. Undoubtedly, the condition of the existing location and interior spaces at institutions in Mashhad need to be improved and enhanced in order to offer a better designing with great consideration given to the development of spatial configuration elements and space area preferred by teenage girls. Design recommendations evaluate architectural design in terms of privacy according teenage girls preferences and economical factors and standards in two levels such as individual and group. Furthermore, this study recommended standards and investigated proper design information such as Interpersonal boundary for teenage girls, size of the study bedroom, the Number of window, the location of bedroom, the size of closet, the number of teenage girls in the study bedroom, the number of washroom and bathroom, spatial privacy in the yard, spatial privacy in a living room, the view of the window, the color of the bedroom, the number of teenage girls in the dormitory and also location of the residential care and neighborhoods.